Exploring the use of choline acetate on the sustainable development of α‑chitin-based sponges - Gomes, J. M. (2020)
This study proposes a green and innovative methodology for the exploitation of natural polymers, namely chitin, using solvents with reduced toxicity for the creation of porous structures with the potential to be used in the biomedical field. Chitin is a promising biopolymer for the design of biodegradable constructs and encouraging developments on its processing have been achieved using ionic liquids (ILs). However, owing to the concerns regarding ILsâ toxicity, biocompatible ILs (Bio-ILs) emerged as a family of ILs with enhanced toxicological features. Herein, we proposed to develop a sustainable route to produce Î±-chitin-based three-dimensional structures using Bio-ILs, namely, choline acetate (Ch[ACE]). Two chitin-based structures were produced based on the presence or absence of the Bio-IL. The characterization of the matrices demonstrated useful morphological features, including porosity (â 85%), interconnectivity (â 98.31%), and high swelling ability. Cytotoxicity assays using the L929 fibroblasts cell line proved the innocuous effect of the Bio-IL on cell metabolic activity when kept in the structures. The nondeleterious effect of Ch[ACE] onto the cells was confirmed when human adipose stem cells were seeded on the surface of the structures. Altogether, the present approach opens new avenues for the design of biomaterials by a sustainable pathway.